The Utilization of the Cake App in Learning Vocabulary in An Islamic Higher Education - Ulfa, Aulia; Ashari, Naufal Ibrahim; Armadita, Baiq Nadya; Ariawan, Soni; Al Viana, Silvi; Abidin, Zainal; Inayah, Salsabila Quranisa (Program Studi Pendidikan Bahasa Inggris, 2025)
This article examines the usefulness of the Cake App in students’ English vocabulary learning. A mixed-methods approach was used to collect data regarding 121 respondents, and questionnaires and interviews were used accordingly, which aimed to evaluate the effectiveness of the Cake App in improving English vocabulary. The findings suggest that the Cake app is a potential tool for vocabulary development since many users reported having enjoyable experiences and making considerable vocabulary increases. The interview findings indicate that users exhibit increased confidence in using new terminology after consistent practice with the interactive aspects of the Cake program. The use of repetition-based learning techniques and contextualization in the films enhanced users' retention of newly acquired vocabulary. Conversely, other limitations were identified, including the lack of a structured curriculum and the significance of video resources. Several users also experienced technical difficulties, including reliance on a steady internet connection. The study results suggest that while the Cake App has the potential to contribute to vocabulary development, more improvements are necessary to maximize its effectiveness as a tool for language learning. The interviews showed that the majority of users deemed the word repetition and speaking practice elements beneficial, improving their comprehension and confidence in using new language. Several users stated that the app assisted them with academic assignments and daily conversations. Nonetheless, there are several challenges were also recognized. Some users saw the app's information as occasionally monotonous particularly owing to the extensive materials provided without a defined learning framework. Moreover, technological limitations pose a significant barrier, particularly for those with limited internet usage or unreliable connections. Several participants said that they are prone to forgetting the stuff they have learned if it is not promptly documented. Consequently, the implementation of an automated note-taking tool or offline mode might enhance the app's efficacy for users seeking to optimize their learning results. These enhancements would not only optimize the Cake App’s effectiveness but also position it as a more comprehensive and structured tool for digital language learning.